The Oxford handbook of Greek and Roman mythography - Smith, R. Scott; Trzaskoma, Stephen M. (Oxford University Press, 2022)
Introduction / R. Scott Smith, Stephen M. Trzsakoma -- The mythographical impulse in early Greek poetry / Pura Nieto -- The origins of mythography as a genre / Jordi Pàmias -- Hellenistic mythography / R. Scott Smith, Stephen M. Trzsakoma -- Imperial mythography / Charles Delattre -- Mythography in Latin / R. Scott Smith -- Mythography in Alexandrian verse / Evina Sistakou -- Antihomerica : dares and dictys / Ken Dowden -- Antoninus Liberalis, Collection of metamorphoses / Charles Delattre -- Apollodorus the Mythographer, Bibliotheca / Stephen M. Trzaskoma -- Conon, Narratives / Manuel Sanz Morales -- Cornutus, Survey of the traditions of Greek theology / Ilaria Ramelli -- Diodorus Siculus, Library / Iris Sulimani -- Heraclitus the Mythographer, On unbelievable stories / Greta Hawes -- Heraclitus the Allegorist, Homeric problems / David Konstan -- Hyginus, Fabulae / Kris Fletcher -- The Mythographus homericus / Joan Pagès -- Other mythography on papyrus / Annette Harder -- Greek mythography and scholia / Nereida Villagra -- Ovid and mythography / Joseph Farrell -- Palaphaetus, Unbelievable tales Hugo Koning -- Parthenius, Erotika pathemata / Christopher Francese -- Pausanias, Description of Greece / William Hutton -- Tragic mythography / Chiara Meccariello -- Rationalizing and historicizing / Greta Hawes -- Allegorising and philosophizing / Ilaria Ramelli -- Etymologizing / Ezio Pellizer -- Catasterisms / Arnaud Zucker -- Local mythography / Daniel Berman -- Mythography and paradoxography / Irene Pajón Leyra -- Mythography and education / R. Scott Smith, Stephen M. Trzsakoma -- Mythography and politics / Lee Patterson -- Mythography and geography / Maria Pretzler -- Mythographer and mythography : indigenous categories? Greek inquiries into the heroic past / Claude Calame -- Mythography and Greek vase painting / Kathryn Topper -- Mythography and Roman wall painting / Eleanor Leach -- Retelling Greek myths on Roman sarcophagi / Zahra Newby -- Mythography and Christianity / Jennifer Nimmo Smith -- Byzantine mythography / Benjamin Garstad -- Mythography in the Latin West / Benjamin Garstad -- Mythography and the reception of classical mythology in the Renaissance, 1340-1600 / Jon Solomon.